Literature Review on Islamic Monetary Policy: Theory, Implementation and Impact - Safira Az Zahro; Haerunnisa Haerunnisa; Riri Aprilia; Fajar Zulfikar Suherman (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Study This study about policy Islamic monetary , which includes base theoretical , implementation in various countries, as well its impact and effectiveness . Policy Islamic monetary , which is based on principles sharia like prohibition usury , emphasis on sectors real , and principle for result , aim For create stability economy and justice socio-economic . The implementation varies in different countries, with some countries implement it system Islamic finance​ full and others using a hybrid model. Research methods used​ is review literature , which involves collection , analysis , and synthesis various source secondary like books , articles journals , and reports relevant research .​ Research result show that policy effective Islamic monetary in control inflation , pushing growth sustainable economy , and improve stability finance . However , challenges still There is in matter standardization practice between countries and integration with system global finance . This study emphasize importance innovation instrument finance sharia and improvement Work The same international For increase effectiveness policy Islamic monetary future .